Solve for x: 3^(4x-3)*5^(7x-4)=3^3x*5^(8x-7).

Expert Answers

An illustration of the letter 'A' in a speech bubbles

We have to solve for x given the equation: 3^(4x-3)*5^(7x-4)=3^3x*5^(8x-7)


=> 3^4x*3^-3*5^7x*5^-4 = 3^3x*5^8x*5^-7

=> (3^4x/3^3x)*(3^-3)*(5^7x/5^8x)*(5^-4/5^-7) = 1

=> (3^x)*(3^-3)*(1/5^x)*(5^3) = 1

=> (3/5)^x = (3/5)^3

As the base is equal we equate the exponent.

=> x= 3

The required value of x is x = 3.

See eNotes Ad-Free

Start your 48-hour free trial to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Get 48 Hours Free Access
Approved by eNotes Editorial